Kombinasi Aerasi-Filtrasi dalam Pengolahan Air Sumur Gali Menjadi Air Bersih - Sinurat, Merry Ananda Pratiwi; Dinanti, Bellinda Dara; Widiya, Widiya; Purnaini, Rizki (Universitas Tanjungpura, 2024)
The increasing population growth will lead to an increased demand for clean water. Homewer, in some areas, people still use raw water from dug wells without any prior treatment. This research aims to develop well water treatment technology using a combination of aeration and filtration systems and to evaluate its effectiveness in reducing iron and turbidity levels in well water. The combination of aeration-filtration technology can achieve a 95% reduction in iron content, with the iron parameter value before treatment being 0,791 mg/L and after treatment being 0,062 mg/L. As for turbidity parameter, it has an effectiveness of 97% with an initial value before treatment of 16 NTU and after treatment becoming 0,355 NTU. This combination technology offers an effective solution to improve water quality with a significant reduction in iron and turbidity parameters.